Outcomes of ICU patients with and without perceptions of excessive care: a comparison between cancer and non-cancer patients - Benoit, Dominique D; van der Zee, Esther N; Darmon, Michael; Reyners, An K L; Metaxa, Victoria; Mokart, Djamel; Wilmer, Alexander; Depuydt, Pieter; Hvarfner, Andreas; Rusinova, Katerina; Zijlstra, Jan G; Vincent, François; et al. (Annals of intensive care, 2021)
BACKGROUND: Whether Intensive Care Unit (ICU) clinicians display unconscious bias towards cancer patients is unknown. The aim of this study was to compare the outcomes of critically ill patients with and without perceptions of excessive care (PECs) by ICU clinicians in patients with and without cancer. METHODS: This study is a sub-analysis of the large multicentre DISPROPRICUS study. Clinicians of 56 ICUs in Europe and the United States completed a daily questionnaire about the appropriateness of care during a 28-day period. We compared the cumulative incidence of patients with concordant PECs, treatment limitation decisions (TLDs) and death between patients with uncontrolled and controlled cancer, and patients without cancer. RESULTS: Of the 1641 patients, 117 (7.1%) had uncontrolled cancer and 270 (16.4%) had controlled cancer. The cumulative incidence of concordant PECs in patients with uncontrolled and controlled cancer versus patients without cancer was 20.5%, 8.1%, and 9.1% (p < 0.001 and p = 0.62, respectively). In patients with concordant PECs, we found no evidence for a difference in time from admission until death (HR 1.02, 95% CI 0.60-1.72 and HR 0.87, 95% CI 0.49-1.54) and TLDs (HR 0.81, 95% CI 0.33-1.99 and HR 0.70, 95% CI 0.27-1.81) across subgroups. In patients without concordant PECs, we found differences between the time from admission until death (HR 2.23, 95% CI 1.58-3.15 and 1.66, 95% CI 1.28-2.15), without a corresponding increase in time until TLDs (NA, p = 0.3 and 0.7) across subgroups. CONCLUSIONS: The absence of a difference in time from admission until TLDs and death in patients with concordant PECs makes bias by ICU clinicians towards cancer patients unlikely. However, the differences between the time from admission until death, without a corresponding increase in time until TLDs, suggest prognostic unawareness, uncertainty or optimism in ICU clinicians who did not provide PECs, more specifically in patients with uncontrolled cancer. This study highlights the need to improve intra- and interdisciplinary ethical reflection and subsequent decision-making at the ICU.
Keywords: Treatment limitation; Cancer; Perception of care; Prognostication; Critical care; ICU; Bias